Two can play - Hazelwood, Ali (Berkley, 2026)
"An enemies-to-lovers spicy novella set in the world of video gaming from the New York Times bestselling author of Problematic Summer Romance-now in print and ebook! Viola Bowen has the chance of a lifetime: to design a video game based on her all-time favorite book series. The only problem? Her colead is Jesse F-ing Andrews, aka her archnemesis. Jesse has made it abundantly clear over the years that he wants nothing to do with her-and Viola has no idea why. When their bosses insist a wintry retreat is the perfect team-building exercise, Viola can't think of anything worse. Being freezing cold in a remote mountain lodge knowing Jesse is right next door? No, thank you. But as the snow piles on, Viola discovers there's more to Jesse than she knew, and heat builds in more ways than one"-- Provided by publisher.